New insights of karyoevolution in the Amazonian turtles Podocnemis expansa and Podocnemis unifilis (Testudines, Podocnemidae). Issue 1 (December 2016) - Noronha, R.; Barros, L.; Araújo, R.; Marques, D.; Nagamachi, C.; Martins, C.; Pieczarka, J.
Abstract Background Cytogenetic studies were conducted in the Brazilian Amazon turtles, Podocnemis expansa Schweigger, 1912 (PEX) andPodocnemis unifilis Troschel, 1848 (PUN) to understand their karyoevolution. Their chromosomal complements were compared using banding techniques (C, G-, Ag-NOR and Chromomycin A3 ) and fluorescence in situ hybridization (FISH), and efforts were made to establish evolutionary chromosomal relationships within the Podocnemidae family. Results Our results revealed that both species have a chromosome complement of 2n = 28. For PEX and PUN, the fundamental numbers (FNs) were 54 and 52, respectively and the karyotypic formulas (KFs) were 24 m/sm + 2st + 2a and 22 m/sm + 2st + 4a, respectively. G-banding evidenced homologies between the two species and allowed identify a heteromorphic pair (chromosome pair 10) in PUN. In PEX, constitutive heterochromatin (CH) was found in the centromeric regions of pairs 1, 2, 4, 6 and 11 and on 9p. In PUN, CH was observed in the centromeric regions of all chromosomes, and in small proximal bands on 1p, 2p, 3q, 4q, 5q, 9q, 10q and 11q. Moreover, CH amplification was seen in one of the homologs of pair 10 (the heteromorphic pair). The CMA3 staining results were consistent with the CH findings. Ag-NOR staining showed that nucleolar organizing regions (NORs) were localized in the pericentromeric region of pair 1 in both species, and this result was confirmed by the 18S rDNA FISH probe. FISH with telomeric probes identified telomeric sequences in the distal regions of all chromosomes. In addition, interstitial telomeric sequences (ITSs) were present in seven chromosome pairs of PUN, perhaps reflecting the amplification of telomere-like sequences. FISH with a probe against the transposable element (TE), Rex 6, revealed that it is dispersed in euchromatic regions of the first chromosome pairs of both species. This is the first report describing the FISH-based analysis of PEX and PUN for the 18S rDNA, Rex 6 and human telomeric sequences. Conclusions Our results contribute to clarifying the chromosomal homologies and rearrangement mechanisms that occurred during the evolution of these species, and may help researchers uncover new markers that will improve our understanding of the taxonomy and systematic classification of Podocnemidae. Trial registration ISRCTNISRCTN73824458 . Registered 28 September 2014. Retrospectively registered.